Militant acts: the role of investigations in radical political struggles - Hoffman, Marcelo (SUNY series in new political science, 2019)
Sources of the militant investigation in Marxism : Marx, Lenin, and Mao -- Workers inquiries from breakaway Trotskyism to Italian workerism -- Badiou, the Maoist investigation, and the party form -- In the shadow of Oedipus : enquêtes in Foucault's theory and practice